Dominican Republic : Fourth Review Under the Stand-By Arrangement and Request for Waiver of Nonobservance of Performance Criterion; Staff Report; Informational Annex; Press Release on the Executive Board Discussion. (IMF Staff Country Reports; Country Report ;, 2011)
In this study, owing to the global financial crisis, a Stand-By Arrangement (SBA) for the Dominican Republic was approved. The aim is to limit the procyclical policies in the short-term and discussions focused on policies necessary to ensure that the end-2011 and 2011 targets are observed. Administrative measures such as proindustria, withholding income tax, and indexation of specific tax are estimated to increase revenues. The conditional cash program 'Solidaridad' is explained. Finally, various issues under the financial program are discussed.